Follow‐up after intensive care treatment: a questionnaire survey of intensive care aftercare in Denmark. Issue 8 (7th July 2017) - Kjer, C. K. W.; Estrup, S.; Poulsen, L. M.; Mathiesen, O.
Abstract : Background: Rehabilitation efforts after treatment in the intensive care unit (ICU) are termed intensive care aftercare. It includes both early in‐hospital follow‐up after ICU‐discharge and late follow‐up after hospital discharge. This study aims to investigate the current ICU‐aftercare activities in Denmark. Methods: We conducted an electronic questionnaire survey, which was distributed by e‐mail to the heads of all 31 general ICUs in Denmark. Specialized ICUs were not included. The questionnaire was divided into the following sections: early ICU‐aftercare, late ICU‐aftercare, future development and demographics. Results: Thirty‐one ICUs were invited to participate. The response rate was 100%. Overall, 26 of 31 ICUs (84%) offered ICU‐aftercare, with the following distribution: early ICU‐aftercare (58%), late ICU‐aftercare (57%) and both (29%). There were no significant associations between hospital size and provision of ICU‐aftercare. For early ICU‐aftercare, the most common eligibility criteria were based on ICU length of stay (LOS) (44%) and a decision based upon doctors' discretion (22%). Incidence of guidelines for early ICU‐aftercare (44%) and checklists at patient contact (35%) were sparse. The most common early ICU‐aftercare items were as follows: respiratory care (82%), tracheostomy care (59%) and nutritional care (59%). For late ICU‐aftercare, the most common eligibility criterion was LOS (41%). Guidelines (71%), but not checklist at patient contact (35%), were more common. Most frequent late ICU‐aftercare interventions were review of ICU‐diaries (59%) and patient charts (53%). Conclusion: Eighty‐four per cent of Danish ICUs offered ICU‐aftercare to their patients. There was an abundant heterogeneity of eligibility criteria and ICU‐aftercare interventions.